Electronic-dimensionality reduction of bulk MoS2 by hydrogen treatment - Cho, Soohyun; Kim, Beom Seo; Kim, Beomyoung; Kyung, Wonshik; Seo, Jeongjin; Park, Min; Jeon, Jun Woo; Tanaka, Kiyohisa; Denlinger, Jonathan D.; Kim, Changyoung; Odkhuu, Dorj; Kim, Byung Hoon; et al. (ROYAL SOC CHEMISTRY, 2018)
A reduction in the electronic-dimensionality of materials is one method for achieving improvements in material properties. Here, a reduction in electronic-dimensionality is demonstrated using a simple hydrogen treatment technique. Quantum well states from hydrogen-treated bulk 2H-MoS2 are observed using angle resolved photoemission spectroscopy (ARPES). The electronic states are confined within a few MoS2 layers after the hydrogen treatment. A significant reduction in the band-gap can also be achieved after the hydrogen treatment, and both phenomena can be explained by the formation of sulfur vacancies generated by the chemical reaction between sulfur and hydrogen.